Ab initio investigations of the binary complexes Rg-IBr (Rg = He, Ne, Ar, Kr, Xe). (March 2018) - Li, Song; Zhai, Yanli; Chen, Peng; Wang, Ning; Chen, Shanjun; Zheng, Rui
Highlights: Ab initio intermolecular PESs of Rg-IBr are constructed. Characteristics of the PESs are identified. Intermolecular vibrational states are assigned. The occurred quantum tunneling effects are discussed. Transition frequencies and spectroscopic constants are predicted. Abstract: Intermolecular interactions, equilibrium parameters, intermolecular vibrational states and spectroscopic constants for the Rg-IBr (Rg = He, Ne, Ar, Kr, Xe) van der Waals complexes are studied theoretically. The equilibrium geometries of global minima for the complex family are characterized by the collinear Rg-I-Br configurations. The local minima of anti-linear Rg-Br-I and nearly T-shaped structures are also located on the potential energy surfaces. The intermolecular vibrational states, average structural parameters and spectroscopic constants for these complexes are determined for each conformer. Interpretations of the characters of the potential energy surfaces reveal the different extent of the anisotropic feature. The probability density distribution of intermolecular vibrational states indicates the quantum tunneling effect is much easier to occur for He- and Ne-IBr owing to their lower barrier height. As for Ar-, Kr- and Xe-IBr complexes, the localization effect enables us to investigate more intermolecular vibrational excited states. The predicted spectroscopic constants of all conformers for each complex are anticipated to fill our knowledge gaps of this complex family.